STUDIES ON CHANGES DURING GROWTH AND DEVELOPMENT OF AONLA (EMBLICA OFFICINALIS GAERTN.) FRUITS cv. NA-7 - SHIKHA PANDEY; BHAGWAN DEEN (The Bioscan, 2025)
The present investigation was carried out during 2023-2024 at the Main Experiment Station, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya (U.P.) in Randomized Block Design (RBD) with four replications. The study aimed to assess the physical and chemical changes that occur during fruit development and to determine maturity indices for optimal harvest. Observations began on August 6, when fruits became visible, and continued at 15-day intervals until maturity. Fruit parameters such as length (4.72-40.16 mm), width (4.92-40.21 mm), weight (0.88-40.32 g), volume (0.29-39.61 cc), pulp content (80.28%-94.28%), fibre (0%-1.60%), and pulp and seed ratio (8.56-21.75) increased steadily. Chemical traits, including TSS (0.5%-9.5%), vitamin C (14.67-603.22 mg/100g), moisture (74.15%-87.68%), TSS/acid ratio (0.45–9.45), reducing sugars (0.53%-4.69%), non-reducing sugars (0.43%-4.29%), and total sugars (0.96%-8.93%), also rose. Conversely, seed content (10.13%-3.34%), specific gravity (1.89-1.20), acidity (2.30%-1.19%), chlorophyll (16.18-3.28 mg/100g), and total phenols (446.63-192.67 mg/100g) declined over the 165 days ending on January 18.